Muhammad 'Abduh and his interlocutors : conceptualizing religion in a globalizing world - Kateman, Ammeke, (Numen Book Series, 2019)
In Muḥammad ʿAbduh and his Interlocutors: Conceptualizing Religion in a Globalizing World , Ammeke Kateman offers an account of Muḥammad ʿAbduh's Islamic Reformism in a context in which ideas increasingly crossed familiar geographical, religious and cultural frontiers. Presenting an alternative to the inadequate perspective of "Westernization", Kateman situates the ideas of Muḥammad ʿAbduh (Egypt, 1849-1905) on Islam and religion amongst those of his interlocutors within a global intellectual field. Ammeke Kateman's approach documents the surprising pluralism of ʿAbduh's interlocutors, the diversity in their shared conceptualizations of religion and the creativity of ʿAbduh's own interpretation. In this way, the conceptualizations of ʿAbduh and his contemporaries also shed light on the diversified global genealogy of the modern concept of religion.